Factors Influencing the Opinion of Patients Concerning the Functioning of the Polish Hospital Before and After Ownership Transformation - Jan Krakowiak PhD; Mateusz Kuzdak MsS; Adam Rzeznicki PhD; Iwona Stelmach MD, PhD, Prof; Alina Kowalska PhD; Wlodzimierz Stelmach MD, PhD (SAGE Publishing, 2014)
Studies of satisfaction among patients are a popular and frequently obligatory tool used in improving the quality of medical services worldwide. Becoming familiar with the opinion of the patients enables to adjust the venue to their expectations, thus contributing to the increase in its competitiveness. We aimed to study patients' satisfaction understood as a tool used in increasing the quality of medical services; in addition, we assessed factors that affect a worse review patients gave about the functioning of this Polish hospital before and after its transformation into a commercial company. The study of satisfaction among patients was conducted using an anonymous questionnaire among 2702 respondents before and 2795 respondents after the hospital's transformation. Multivariate logistic regression analysis was applied to statistically analyze the collected empirical material, where the dependent variable was a worse evaluation of respondents concerning the functioning of the hospital. It was demonstrated that both before and after the hospital's transformation into a commercial company, it was education and conditions of housing of patients that determined their opinion about the functioning of the admission center and hospital wards. A higher level of education increases the risk of a worse evaluation of the admission center and hospital wards, whereas higher self-evaluation of housing conditions lowered the discussed risk. Factors that influence the opinion of patients concerning the functioning of the hospital are education, age, marital status, housing conditions of the respondents and also the number of stays at a given hospital, and a conscious choice of the facility in which a patient wished to be treated.